Efficient Colorimetric Fluoride Anion Chemosensors With Varied Colors Based on Simple Aminobenzodifuranone Organic Π-Conjugated Dyes - Deng, Zhi Feng; Li, Rui; Geng, Jie Ting; Zheng, Meng; Li, Lei Quan; Shi, Xin; Ren, Wen Qi; Meng, Zi Yue; Ji, Zhuo Ting; Hua, Jing (Frontiers in Chemistry, 2020)
The detection of fluoride anion (F–) with high selectivity and sensitivity in an organic solution with naked eye has always been challenge. In this investigation, the simple compound based on aminobenzodifuranone (ABDF) was designed and synthesized. The deprotonation of amino moiety caused by F– is responsible for the color change from dark blue to varied colors (colorless, yellow, orange, red) in different common organic solvents with the UV/vis spectra over 200 nm blue-shifted. The color changing is quite sensitive to the naked eye under ambient light. The detection limit for F– could reach the concentration as low as 10-6 M with high selectively even in a solution containing multi anions.